2022
DOI: 10.3390/ijms23126570
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Analysis of Genes Involved in the GA Signal Transduction Pathway in ‘duli’ Pear (Pyrus betulifolia Bunge)

Abstract: Gibberellic acid (GA) is an important phytohormone that regulates every aspect of plant growth and development. While elements involved in GA signaling have been identified and, hence, their functions have been well studied in model plants, such as Arabidopsis and rice, very little is known in pear. We, therefore, analyzed the genes related to GA signaling from the recently sequenced genome of the wildtype ‘duli’ pear (Pyrus betulifolia Bunge), a widely used rootstock for grafting in pear cultivation in China … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 50 publications
(74 reference statements)
0
1
0
Order By: Relevance
“…The Pc(S)-GA2ox unigene is involved in the conversion of its inactive form, indicating that GA 3 prevented GA biosynthesis and promoted its degradation in leaves of P. chinense Schneid seedlings [49,50]. The GID1B/C proteins as receptors recognized GA 3 that combined with DELLA protein to form a trimer, subsequently labeled by SCF SLY1 /GID2 complex and degraded through 26S protease, releasing the repression of DELLA protein and promoting cell elongation in plants [51,52]. Thus, the expression variations of Pc(S)-GID1/2 (downregulation) and Pc(S)-DELLA (upregulation) unigenes demonstrated that exogenous GA 3 inhibited the GA signal transduction in leaves of P. chinense Schneid seedlings, speculating that GA 3 may promote its growth by other phytohormones.…”
Section: Discussionmentioning
confidence: 99%
“…The Pc(S)-GA2ox unigene is involved in the conversion of its inactive form, indicating that GA 3 prevented GA biosynthesis and promoted its degradation in leaves of P. chinense Schneid seedlings [49,50]. The GID1B/C proteins as receptors recognized GA 3 that combined with DELLA protein to form a trimer, subsequently labeled by SCF SLY1 /GID2 complex and degraded through 26S protease, releasing the repression of DELLA protein and promoting cell elongation in plants [51,52]. Thus, the expression variations of Pc(S)-GID1/2 (downregulation) and Pc(S)-DELLA (upregulation) unigenes demonstrated that exogenous GA 3 inhibited the GA signal transduction in leaves of P. chinense Schneid seedlings, speculating that GA 3 may promote its growth by other phytohormones.…”
Section: Discussionmentioning
confidence: 99%
“…Two pear varieties, ‘duli’ pear ( Pyrus betulifolia Bunge) and Korla fragrant pear, were used to evaluate the biocontrol activity of antagonistic bacteria against E. amylovora. The detached leaves and twigs were selected from ‘duli’ pear, a wildtype pear widely used rootstock for grafting in China due to its resistance to biotic and abiotic stress ( Song et al, 2022 ). The fruits were collected from Korla fragrant pear ( Pyrus sinkiangensis Yü), a popular cultivated pear variety in China.…”
Section: Methodsmentioning
confidence: 99%